Predicting Wisdom Based on Peer Relationships and Presence in Virtual Spaces - Alnuaimi, Alaa Sabah Mohammed; Yousefi, Zahra; Aayedi, Ali Enad Zamil; Golparvar, Mohsen (International Journal of Education and Cognitive Sciences, 2022)
Purpose: This study aimed to investigate the relationship between wisdom, peer relationships, and the time spent in virtual spaces among university students. Methods and Materials: A descriptive-correlational research design was used. The sample consisted of 350 students from Wasit University, selected via convenience sampling. Participants completed three questionnaires: the Ardelt Wisdom Scale (2003) to assess wisdom, the Peer Relationship Questionnaire (Hudson, 1997) to evaluate peer interactions, and a single-item measure of time spent in virtual spaces. Pearson correlation analysis was conducted to explore relationships between variables, and stepwise regression analysis was used to identify predictors of wisdom. Data were analyzed using SPSS-27. Findings: The results revealed a significant positive correlation between peer relationships and wisdom , indicating that stronger peer interactions are associated with higher wisdom levels. Conversely, time spent in virtual spaces showed a significant negative correlation with wisdom (r = -0.725, p < 0.001), suggesting that more time online is linked to lower wisdom scores. Stepwise regression analysis demonstrated that time spent in virtual spaces was the strongest predictor of wisdom, explaining 52.6% of the variance, while peer relationships accounted for an additional 3.3%. Conclusion: The study concludes that peer relationships play a crucial role in the development of wisdom, whereas excessive online engagement may detract from it. The findings highlight the need for balanced digital engagement and strong peer interactions to foster cognitive, reflective, and emotional growth. Future research should explore the quality of online interactions and the role of various types of relationships in wisdom development.